The future of piped water. Issue 7 (17th November 2021) - Milman, Anita; Kumpel, Emily; Lane, Kaycie
ABSTRACT: While the past decades have seen substantial gains in access to safe drinking water around the world, the challenge over the next 50 years will be to maintain and expand these gains. Ageing infrastructure, deferred maintenance and financial woes, combined with shifting demands and climate change, threaten the functioning and long-term sustainability of water systems. This article examines three facets of piped water supply – infrastructure, management and financing – assessing the stressors, drivers of change and paradigm shifts affecting each. The review sheds light on the future of piped water, the successes that may be found and the remaining gaps to be addressed.